Higher exposure to childhood adversity associates with lower adult flourishing - Lin Wang; Zhiyuan Yu; Wenyi Chen; Juan Zhang; Amie F. Bettencourt (BMC, 2022)
Abstract Background Adverse childhood experiences (ACEs) are prevalent and associated with negative health and social outcomes. However, our understanding of how patterns of ACEs exposure relate to positive outcomes in adulthood remains limited. This study aims to identify patterns of ACEs and examine associations with flourishing in a sample of Chinese young adults. Methods This cross-sectional study was conducted from August to November 2020. Young adults, ages 18-35, enrolled in undergraduate or graduate programs at universities in Mainland China were recruited through convenience and snowball sampling to participate in a survey. The exposure to ACEs was measured by the twelve-item Chinese version of the ACE-International Questionnaire. Additional measures included six domains of flourishing assessed using the Chinese version of the Flourishing Measure, and demographic covariates (i.e., gender, age, year in university, marital status). Descriptive statistical analysis and latent class analysis (LCA) were performed using SPSS 27 and Mplus 8.5. Results Participants included 9468 young adults (mean age = 20.1 years). Majority of participants were female (75.3%), undergraduate students (96.4%), and single (79.8%). Approximately 56% of participants reported at least one ACE; 7.0% reported four or more ACEs. Emotional neglect (33.2%), household violence (20.6%), and parental separation/divorce (13.9%) were the most frequently reported ACEs. LCA identified three ACEs classes: multiple maltreatment and household violence (4.7%), emotional neglect and household violence (16.2%), and low ACEs (79.1%). Individuals in the low ACEs class had the highest level of flourishing whereas individuals in multiple maltreatment and household violence had the lowest level of flourishing in all six domains. There were no significant differences in flourishing between the multiple maltreatment and household violence and the emotional neglect and household violence classes except in the physical and mental health (means = 6.17 vs 6.51, p = 0.02) and the financial and material stability domains (means = 5.25 vs 5.66, p = 0.04). Conclusions Patterns of multiple ACEs exposures were associated with lower levels of flourishing. Our findings have implications for efforts to prevent ACEs exposure through monitoring and promoting family well-being and routine screening to identify those with ACEs exposure to prevent negative social and health sequelae.